A study on correlating reduction in Poisson's ratio with transverse crack and delamination through acoustic emission signals. (October 2017) - Yilmaz, C.; Yildiz, M.
Abstract: During the uniaxial loading of fiber reinforced polymer (FRP) composites, Poisson's ratio (νxy ), which is a constant elastic property for isotropic materials, decreases significantly. Micro-damage created within FRP composites as a result of an applied stress causes this decrease. As the level of micro-damage increases, a greater level of reduction in Poisson's ratio occurs. FRP composites, in general, show three main micro-damage types under uniaxial tensile loading, namely, transverse crack, delamination and fiber rupture. To determine micro-damage types which dominantly affects the relevant reduction in Poisson's ratio, glass fiber reinforced cross-ply laminates with three different off-axis ply content are produced and then tested under a uniaxial tensile loading. The Acoustic Emission (AE) signals are concurrently recorded and grouped into three clusters in accordance with their frequency, which is either associated with transverse crack, delamination or fiber rupture. The frequency based clustering of AE signal facilitates detailed investigation of delamination onset and effect of different micro-damage types on Poisson's ratio. It is proven that stacking sequences with a higher number of transverse cracks and delaminations, quantified based on AE signals, show a greater reduction in Poisson's ratio.